Odpowiedzi

2009-12-08T18:28:40+01:00
1) tutaj proponuje metodę podstawiania
y=2x+1
4x+y=13

y=2x+1
4x+2x+1=13

y=2x+1
6x+1=13 / -1

y=2x+1
6x=12 / 6

y=2x+1
x=2

y=2*2+1= 4+1=5
x=2

x=5
y=2


2) tutaj tez metoda podstawiania
5y-x=3
x=3-y

5y-(3-y)=3 zmiana znakow bo przed nawiasem mamy minus
x=3-y

5-3+y=3
x=3-y

2+y=3 /-2
x=3-y

y=1
x=3-1=2

x=2
y=1
1 5 1
2009-12-08T18:31:04+01:00
Y=2x+1
4x+y=13

4x+ 2x+1=13
6x=12/:6
x=2
y= 2*2+1=5

5y-x=3
x=3-y

5y - (3-y)=3
5y-3+y=3
6y=6/:6
y=1
x=3-1=2
  • Użytkownik Zadane
2009-12-08T19:26:44+01:00
Y=2x+1
4x+y=13

4x+ 2x+1=13
6x=12/:6
x=2
y= 2*2+1=5

5y-x=3
x=3-y

5y - (3-y)=3
5y-3+y=3
6y=6/:6
y=1
x=3-1=2